How would you explain how to do this problem step

  1. Explain how I would organize my step by step calculations in evaluating the order of operations problem below. (Remember PEMDAS)
    1. answers icon 1 answer
    2. views icon 123 views
  2. Step 1) Write the problem down EXAMPLE: 3x + 4 = 54*with the problem number Step 2) Solve step-by-step 3x +4 -4 = 54-4 *Show
    1. answers icon 1 answer
    2. views icon 82 views
  3. I need someone to explain to me step by step the process of this problem its in my book as an example but i am not understanding
    1. answers icon 0 answers
    2. alma20 asked by alma20
    3. views icon 1,170 views
  4. PLEASE HELP! I got this problem wrong and I would really like to understand how to do it for future reference. The problem can
    1. answers icon 1 answer
    2. Stacy asked by Stacy
    3. views icon 249 views
  5. would you help me write a logic application forandy has the cards1,5,and 7 belle has the crds 5,4,and 7 carol has the cards 2,4
    1. answers icon 0 answers
    2. deborah cobb asked by deborah cobb
    3. views icon 583 views
  6. A student solves the following problem:Problem: 2(x - 3) + 3x = 19 Step 1: 2x - 6 + 3x = 19 Step 2: (2x + 3x) - 6 = 19 Step 3:
    1. answers icon 1 answer
    2. views icon 22 views
  7. A student solves the following problem:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
    2. views icon 17 views
  8. A student solves the following problem:Problem: 2(x−3) + 3x = 19 Step 1: 2x − 6 + 3x = 19 Step2: (2x + 3x) −6 = 19 Step 3:
    1. answers icon 1 answer
    2. views icon 77 views
  9. A student solves the following problem:Problem: 2(x-3) + 3x = 19 Step 1: 2x - 6 + 3x = 19 Step2: (2x + 3x) -6 = 19 Step 3: 5х -
    1. answers icon 1 answer
    2. views icon 75 views
  10. A student solves the following problem:Problem: 2(x−3) + 3x = 19 Step 1: 2x − 6 + 3x = 19 Step2: (2x + 3x) −6 = 19 Step 3:
    1. answers icon 1 answer
    2. views icon 132 views